M33. ATTENTUATED POSITIVE SYMPOMS AND FACIAL AFFECT PROCESSING IN HIGH-RISK ADOLESCENTS WITH AND WITHOUT AUTISM. (18th May 2020) - Maat, Arija; Therman, Sebastian; Swaab, Hanna; Ziermans, Tim
Abstract: Background: Autism and schizophrenia spectrum disorders both represent severely disabling neurodevelopmental disorders with marked impairments in social functioning. Despite an increased incidence of psychosis in autism, and substantial overlap in symptoms and cognitive markers, it is unclear whether such phenotypes are specifically related to risk for psychosis or perhaps reflect more general, idiosyncratic autism traits. Attenuated positive symptoms (APS) currently constitute the best and most-replicated clinical predictors of schizophrenic psychosis, and are common in clinical youth with and without autism. The aims of this study were to test the hypothesis that facial affect processing is impaired in adolescents with APS and to explore whether such deficits are more indicative of psychotic or autistic phenotypes on a categorical and dimensional level. Methods: Fifty-three adolescents with APS and 81 typically developing controls (aged 12–18) were included. The APS group consisted of adolescents with (n = 21) and without (n = 32) a diagnosis of autism spectrum disorder. Facial affect recognition and 'lower-level' cognitive skills, namely pattern and face recognition, were assessed with the Amsterdam Neuropsychological Tasks. For associations with schizotypal and autistic-like traits the Schizotypal Personality Questionnaire and Social Communication questionnaire were used and one-dimensional factor scores were generated with confirmatory factor analysis. Results: Our preliminary findings suggest that APS in adolescents is not associated with impairments in pattern, face, or emotion recognition. However, the APS group with autism spectrum disorder generally showed slower reaction times for face/emotional stimuli and they were significantly worse in recognizing fearful expressions than APS participants without autism spectrum disorder and controls. There were no dimensional correlations with schizotypal traits and marginal correlations between autistic-like traits and speed of recognizing faces. Discussion: Contrary to our expectations, APS demonstrated limited use in identifying cognitive deficits typical to schizophrenic psychosis. A more autistic-like profile may be characterized by slower reaction times to facial stimuli, suggesting that more complicated and dynamic social cognitive stimuli have a better chance of discerning between autistic and psychotic-like phenotypes.